An L-tert-leucine derived urea catalyzed asymmetric synthesis of acylclic N, N′-ketals derived from aryl amines and isatin-derived ketimines. (1st January 2022) - Liu, Shuo; Wang, Jingdong; Wei, Zhonglin; Cao, Jungang; Liang, Dapeng; Lin, Yingjie; Duan, Haifeng
Abstract: An asymmetric synthesis of N, N′ -ketal compounds derived from isatin-derived ketimines and aryl amines has been developed using an inexpensive and readily available L-tert -leucine derived urea catalyst. Using this asymmetric catalytic synthetic method, a series of 3-substituted 3-amino-2-oxoindole derivatives containing an N, N ′-ketal motif were obtained in high yields with high enantioselectivities. Graphical abstract: Image 1